Electrocatalytic reduction of furfural for selective preparation of 2-methylfuran over a sandwich-structured Ni-Cu bimetallic catalyst - Cui, Yiming; Wang, Ze; Li, Songgeng (The Korean journal of chemical engineering, 2023)
The electrocatalytic reduction (ECR) of furfural (FF) for synthesis of 2-methylfuran (MF) is investigated, using a sandwich-structured electrode (NiCu/CalZIF/CP), with an inner substrate of carbon paper (CP), a surface layer of Ni-Cu bimetallic catalyst (metal layer), and a middle layer of calcined Ni-ZIF-8 (CalZIF) particles. It is found that the production rate (PR) and Faradaic efficiency (FE) of MF increase with the increase of metal loading, while the variation becomes stable in higher dosages. The FE of MF illustrates a rising-first-and-declining-later trend with the increase of current density, but in a slight degree compared with the system without CalZIF, indicating a better stability on anti-interference of current. The PR of MF increases with increasing current first and then becomes stable, which differs to the reducing trend in higher currents in the system without CalZIF. Under the optimized conditions with H 2 SO 4 concentration of 0.2 M and current density of 12 mA·cm −2 , the total FE of organics, the FE of MF, and the PR of MF, respectively reach to their maximum values of 82%, 66% and 75 µmol·cm −2 ·h −1 , under the catalytic effects of the composite electrode with optimal Ni/Cu ratio of 0.04, metal layer loading amount of 3 mg·cm −2 , and CalZIF dosage of 1 mg·cm −2 . The electrode can be regenerated after re-elctrodeposition treatment. The deactivation of catalyst is found relative to the loss and agglomeration of the metals, which is resulted from the corrosion and rearrangement of the metal atoms over the electrode surface.